Depression prevention in healthcare workers during the COVID-19 pandemic. (17th January 2022) - Takada, H; Ae, R; Ogawa, M; Kagomoto, T
Abstract: Background: Few studies have assessed depression in healthcare workers (HCWs) in Japan owing to the coronavirus disease 2019 (COVID-19) pandemic, and no studies have proposed effective interventions to help support their mental health. Aims: To test the hypothesis that enhancing access to mental healthcare professionals helps to improve HCWs' mental health. Methods: This cross-sectional study assessed depressive symptoms in HCWs at three hospitals in Osaka prefecture between May and July, 2020. The survey obtained information on HCWs' mental state and related situations/perceptions. Multivariable logistic regression analysis was performed to identify factors associated with depressive symptoms. Results: Of the 3291 eligible HCWs, 1269 (39%) completed the survey. Of all HCWs, 87 (7%) were physicians, and 700 (55%) were nurses. A total of 181 (14%) HCWs had moderate-to-severe symptoms of depression. Being a frontline worker was not significantly associated with depressive symptoms (odds ratio: 0.86 [95% confidence intervals: 0.54–1.37], P = 0.50). The unwillingness to consult with anyone was significantly associated with more severe depressive symptoms (1.70 [1.10–2.63], P < 0.01). HCWs who had no opportunity to confide in family/friends (1.66 [1.10–2.52], P < 0.01) or colleagues/supervisors (3.19 [2.22–4.58], P < 0.001) were significantly more likely to have depressive symptoms. Conclusions: Being a frontline HCW in a Japanese hospital treating patients with COVID-19 was not significantly associated with having depressive symptoms. The study highlights that encouraging daily communication with close persons (family, friends, colleagues and supervisors), rather than improving access to mental health professionals, might help to prevent depression in HCWs during the COVID-19 pandemic.